The Effect of Whatsapp-Based Nutrition Education on Anemia Knowledge and Attitudes Among Female Adolescents In Pidie District - Nurzinah, Risa; Al Rahmad, Agus Hendra; Arifin, Syuja’ Rafiqi (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
Anemia remains a major public health concern in Indonesia, affecting individuals across all age groups, particularly women and adolescents. According to Basic Health Research (2018), anemia prevalence among women is 48.9%. In Pidie Regency, the prevalence of Iron Deficiency Anemia (IDA) remains high, largely due to low compliance with iron supplement consumption among adolescents. This study aimed to analyze the effect of WhatsApp-based nutrition education on knowledge and attitudes regarding anemia among female adolescents. This quasi-experimental study applied a one-group pretest–posttest design with a non-probability quota sampling method. A total of 42 female adolescents participated. Data were collected using validated structured questionnaires administered before and after the intervention. Nutrition education was delivered through WhatsApp media, focusing on anemia prevention and management. Paired t-test was employed to analyze differences between pretest and posttest scores. Results showed a significant improvement in knowledge, with a mean increase of 10.47 points from baseline (p = 0.000). Attitude scores also improved significantly, with a mean increase of 1.19 points (p = 0.001, t = 3.89, SD = 1.40). Overall, the average knowledge improvement reached 10.5 points after the intervention. In conclusion, WhatsApp-based nutrition education proved effective in enhancing both knowledge and attitudes about anemia among female adolescents. This digital health promotion approach offers an accessible, cost-effective, and practical strategy that can be adopted by nutritionists and health workers to strengthen education programs and encourage positive behavior change for anemia prevention.